"Blonde makes you strong": Embodiment, intersubjectivity, and feminist reflexivity. (June 2023) - Motzafi-Haller, Pnina
Drawing on theoretical discussions that explore embodiment as a critical realm for the articulation of subjugated agency, I focus in this paper on the manner in which hair color has become a visual sign, a code that marks social boundaries and gendered ethno-class identities in contemporary Israel. Empirically, this essay aims to explore the manner in which Mizrahi women craft their own subjectivity in relation to dominant discourses through their blonde embodied practice. Using three ethnographic vignettes I argue that the blonde performance of my interlocutors cannot be understood as mere mimicry of, or reaction to, the imagined Israeli collective identification as White European. It is rather a creative act of self-fashioning that brings joy and self-affirmation to its practitioners and at the same time, at a collective level, it is a practice that poses a symbolic threat that works to fragment hegemonic Israeli claims to Whiteness